Analisis Faktor Gaya Hidup yang Berkontribusi terhadap Kejadian Obesitas pada Remaja - Afriyani Dengo; Edwina Rugaiah Monayo; Nur Ayun R. Yusuf (Journal of Telenursing (JOTING), 2026)
This study aimed to identify lifestyle factors contributing to obesity among adolescents at MAN 1 Gorontalo City. The study employed a quantitative method with a descriptive correlational design and a cross-sectional approach. The results showed significant relationships between physical activity and obesity incidence (p-value = 0.000), dietary patterns and obesity incidence (p-value = 0.001), as well as sleep patterns and obesity incidence (p-value = 0.001). In conclusion, physical activity, dietary patterns, and sleep patterns are lifestyle factors associated with obesity among adolescents at MAN 1 Gorontalo City. Lower levels of physical activity, poorer dietary habits, and inadequate sleep patterns increase the risk of obesity among adolescents.   Keywords: Lifestyle Factors, Obesity, Adolescents